THE INFLUENCE OF CAREER DEVELOPMENT AND PERFORMANCE EVALUATION ON EMPLOYEE JOB SATISFACTION IN THE PRINTING INDUSTRY - Indrawati, Dwi Rizqiani; Sestri G , Francisca; Anwar , Moh Nuril; Winanti, Winanti; Imeliyanti , Eka; Santi , Neta Mirda (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research investigates how career development and performance evaluation influence employee job satisfaction inside of the Production Division of the printing industry. The study is grounded in the premise that both career advancement opportunities and systematic performance assessments play a critical role in fostering a supportive work environment that promotes employee satisfaction. This study employs a quantitative research method utilizing an associative approach. Data were gathered by administering questionnaires to 153 participants, all of whom are employees inside of the production division. Data analysis involved testing for validity and reliability, followed by multiple linear regression analysis, including t-tests, F-tests, and determination of the coefficient of determination. The outcomes reveal that both career development and performance evaluation have a positive and statistically significant impact on employee job satisfaction, both personally and collectively. Career development contributes to increasing motivation and loyalty, while fair performance evaluation encourages work enthusiasm and better performance. The conclusion of this study is that career development and performance evaluation are two important factors that need to be considered by management to improve employee job satisfaction in the company.